Synthesis and characterization of the photophysical properties of novel heterocyclic imines - Castro, M. C. R. (2015)
As part of an on-going research to develop efficient heterocyclic systems for optical applications (NLO, photochromic, chemosensor, etc) we report in this work the synthesis and the photophysical characterization of novel heterocyclic imines 1a-b and 2, functionalized with thiadiazole or benzothiazole as acceptor groups linked to an aryl ring.